Differential expression of mouse beta/goat beta c, mouse beta/goat beta F, and mouse beta/goat epsilon II hybrid globin genes in murine erythroleukemia cells. - Kerlakian, C B (Mol Cell Biol, 1986)
We assembled three hybrid beta-globin genes by fusing the mouse beta-major promoter and initial transcribed region to one of three goat beta-like globin gene bodies: beta c (preadult), beta F (fetal), or epsilon II (embryonic). Thymidine kinase (tk)-deficient murine erythroleukemia (MEL) cells were cotransformed with one of these constructs and a separate plasmid bearing the tk gene. Half of the 24 cell lines containing either the mouse beta/goat beta c or mouse beta/goat beta F genes expressed the transferred genes at significant levels; in many cases the hybrid genes were, like the endogenous beta-globin genes, inducible with dimethyl sulfoxide. We obtained 13 cell lines containing the mouse beta/goat epsilon II hybrid gene, 6 of which were cotransfected with a mouse beta/human beta fusion gene known to function in MEL cells. In contrast to the results with the other fusion genes, the mouse beta/goat epsilon II hybrid was very poorly expressed: in two separate experiments, 0 of 13 and 2 of 13 lines showed significant mouse beta/goat epsilon II RNA levels after induction. In all these lines the endogenous mouse beta and cotransfected mouse beta/human beta genes were expressed. As an initial test of possible reasons for the inactivity of the mouse beta/goat epsilon II hybrid, we recloned this fusion gene into a tk-bearing plasmid, adjacent to the tk gene. Of 12 cell lines transformed with this plasmid, 11 produced mouse beta/goat epsilon II RNA; in 6 cases the expression was both strong and dimethyl sulfoxide inducible. IMAGES: